Peran Strategis Pendidikan Agama Islam Madrasah dalam Pembentukan Karakter Remaja di Tengah Tantangan Globalisasi - Muslimah, Kiki Cahya; Kristiana , Anna; Kurniawati, Euis (UIR Press, 2025)
Islamic Religious Education (IRE) in madrasahs plays a strategic role in shaping adolescent character amid the challenges of globalization characterized by value pluralism and moral decline. This study aims to analyze the role of Islamic Religious Education in madrasahs in fostering adolescent character through the perspectives of values education and moral development. The study employs a qualitative approach using a library research method, drawing on academic books and peer-reviewed journal articles on Islamic education, character education, and adolescent moral development, mainly published within the last five years. The findings indicate that Islamic Religious Education in madrasahs significantly contributes to adolescent character formation through moral value internalization, moral identity development, strengthened self-control, and enhanced moral resilience against global influences. Islamic Religious Education also functions as a protective factor against deviant behavior and promotes prosocial attitudes among adolescents. This study highlights the importance of strengthening Islamic Religious Education as a holistic and contextual values-based education within madrasah education policies.